Nation and migration: a critical review of textbooks for high school education in Argentina - Taboada, Beatriz Maria (Romanica Olomucensia, 2016)
This article goes deeper into some of the findings of a previous research study named ``'Nosotros, los argentinos': la construccion de la identidad nacional en libros de texto de Ciencias Sociales'' (``'We, the Argentine people': the construction of national identity in Social Science textbooks''), where the way in which such an identity is discursively constructed in textbooks aimed at high school education was analyzed. One of the axes prioritized in the analysis is the construction of migratory processes related to the national territory, an aspect which will be considered in this article. In the suggested focus we made use of theoretical and methodological tools from the Discourse-Historical Approach, to account for certain regularities present in the approach to migration processes in the textbooks currently being used in educational institutions in Argentina.
Keywords: textbook; nation; migration; school; Argentina; Discourse-Historical Approach.